2014
DOI: 10.1158/1078-0432.ccr-13-2391
|View full text |Cite
|
Sign up to set email alerts
|

Nondisruptive p53 Mutations Are Associated with Shorter Survival in Patients with Advanced Non–Small Cell Lung Cancer

Abstract: Purpose: TP53 mutations in early-stage non-small cell lung cancer (NSCLC) may be associated with worse survival but their prognostic role in advanced NSCLC is controversial. In addition, it remains unclear whether mutated patients represent a clinically homogeneous group.Experimental Design: We retrospectively examined TP53 mutations and outcome in a training cohort of 318 patients with stage IIIB-IV NSCLC: 125 epidermal growth factor receptor (EGFR) wild-type (wt) and 193 EGFR mutated (mut). An independent va… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
149
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(173 citation statements)
references
References 45 publications
15
149
2
Order By: Relevance
“…In breast cancer, for example, it is well established that missense mutations affecting DNA binding are associated with worse patient survival than missense mutations outside of DNA-binding motifs (Olivier et al 2006). It has since become apparent that the specific functional properties of p53 mutant proteins play a key role in conferring several tumor types with poor prognosis and therapeutic resistance (Poeta et al 2007;Govindan and Weber 2014;Molina-Vila et al 2014;Brachova et al 2015). Crystallographic studies focused on the interaction of p53 and its cancer-associated mutants with DNA have led to a classification system that defines mutations occurring in the p53-DNA-binding surface as contact mutations Mutations are classified as substitution, deletion, insertion, or complex mutations.…”
Section: Functional Classification Of Tp53 Mutations and Their Clinicmentioning
confidence: 99%
“…In breast cancer, for example, it is well established that missense mutations affecting DNA binding are associated with worse patient survival than missense mutations outside of DNA-binding motifs (Olivier et al 2006). It has since become apparent that the specific functional properties of p53 mutant proteins play a key role in conferring several tumor types with poor prognosis and therapeutic resistance (Poeta et al 2007;Govindan and Weber 2014;Molina-Vila et al 2014;Brachova et al 2015). Crystallographic studies focused on the interaction of p53 and its cancer-associated mutants with DNA have led to a classification system that defines mutations occurring in the p53-DNA-binding surface as contact mutations Mutations are classified as substitution, deletion, insertion, or complex mutations.…”
Section: Functional Classification Of Tp53 Mutations and Their Clinicmentioning
confidence: 99%
“…At least in NSCLC, the prognostic role of the TP53 gene is controversial and not all mutated patients represent a clinically homogeneous group (11). We have found that "nondisruptive" TP53 mutations, may apparently confer oncogenic activities to the mutated p53 protein, and define a group of metastatic NSCLC patients with a dismal prognosis (11). In contrast, patients with 'disruptive' TP53 mutations characterized by a complete, or almost complete, loss of activity of the p53 protein, have good prognosis, similar to patients with wild-type TP53 (11).…”
mentioning
confidence: 93%
“…We have found that "nondisruptive" TP53 mutations, may apparently confer oncogenic activities to the mutated p53 protein, and define a group of metastatic NSCLC patients with a dismal prognosis (11). In contrast, patients with 'disruptive' TP53 mutations characterized by a complete, or almost complete, loss of activity of the p53 protein, have good prognosis, similar to patients with wild-type TP53 (11). In the study of Dowlati et al, SCLC patients with 'disruptive' TP53 mutations had a significantly better response to first-line chemotherapy compared to patients with wild-type TP53.…”
mentioning
confidence: 99%
“…In addition, no significant correlation was observed between the expression of p53 and PFS. A previous study reported that non-disruptive mutations in the TP53 gene are an independent prognostic factor of shorter survival rates in advanced NSCLC (37), whereas another study showed that p53 mutations are significantly correlated with tumor relapse in patients with stage I disease (38). The tumor suppressor gene, TP53, is the most frequently mutated gene in NSCLC (39).…”
Section: A B C Dmentioning
confidence: 99%